2012
DOI: 10.1136/bmjopen-2012-001721
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for injury mortality in rural Tanzania: a secondary data analysis

Abstract: BackgroundInjuries rank high among the leading causes of death and disability annually, injuring over 50 million and killing over 5 million people globally. Approximately 90% of these deaths occur in developing countries.ObjectivesTo estimate and identify the risk factors for injury mortality in the Rufiji Health and Demographic Surveillance System (RHDSS) in Tanzania.MethodsSecondary data from the RHDSS covering the period 2002 and 2007 was examined. Verbal autopsy data was used to determine the causes of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
5
11
0
Order By: Relevance
“…The overall 31.98/100,000 age-standardized mortality rate due to injuries in this study was similar to that reported in a population-based study in a rural district of Tanzania [39]. It has already been reported that more males than females are likely to die from injuries than women [39]. A previous descriptive analysis of road tra c injuries in Tanzania has shown that between 1990 and 2000 the number of RTI rose by 44% and that of death by 64% [32].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The overall 31.98/100,000 age-standardized mortality rate due to injuries in this study was similar to that reported in a population-based study in a rural district of Tanzania [39]. It has already been reported that more males than females are likely to die from injuries than women [39]. A previous descriptive analysis of road tra c injuries in Tanzania has shown that between 1990 and 2000 the number of RTI rose by 44% and that of death by 64% [32].…”
Section: Discussionsupporting
confidence: 87%
“…Road tra c injuries (RTI) have been reported to account for the largest proportion of unintentional injuries in low-and middle-income countries [61]. The overall 31.98/100,000 age-standardized mortality rate due to injuries in this study was similar to that reported in a population-based study in a rural district of Tanzania [39]. It has already been reported that more males than females are likely to die from injuries than women [39].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This huge sex disparity cannot be attributable to population profile but rather due to characteristics inherent in males [19]. Males have consistently been shown to be at a higher risk of injury and lifestyle and behavioral factors may be responsible [20,21]. The male proportion found is however larger than what has been reported in other studies; Rwanda 57% [15], Finland 75% [22] and Ethiopia 79% [23].…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, male death was dominant. Traffic accident in England and Hussain et (7,(9)(10)(11)(12). In our study, due to its low rates (2 cases) penetrating trauma was not evaluated.…”
Section: Discussionmentioning
confidence: 99%